Grand Challenges in the Management and Conservation of North American Inland Fishes and Fisheries. Issue 2 (19th February 2017) - Lynch, Abigail J.; Cooke, Steven J.; Beard, T. Douglas; Kao, Yu‐Chun; Lorenzen, Kai; Song, Andrew M.; Allen, Micheal S.; Basher, Zeenatul; Bunnell, David B.; Camp, Edward V.; Cowx, Ian G.; Freedman, Jonathan A.; et al.
Abstract : Even with long‐standing management and extensive science support, North American inland fish and fisheries still face many conservation and management challenges. We used a grand challenges approach to identify critical roadblocks that if removed would help solve important problems in the management and long‐term conservation of North American inland fish and fisheries. We identified seven grand challenges within three themes (valuation, governance, and externalities) and 34 research needs and management actions. The major themes identified are to (1) raise awareness of diverse values associated with inland fish and fisheries, (2) govern inland fish and fisheries to satisfy multiple use and conservation objectives, and (3) ensure productive inland fisheries given nonfishing sector externalities. Addressing these grand challenges will help the broader community understand the diverse values of inland fish and fisheries, promote open forums for engagement of diverse stakeholders in fisheries management, and better integrate the inland fish sector into the greater water and land use policy process.